2016
DOI: 10.1159/000446571
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nephroprotective Efficacy of Hypoxic Preconditioning in Patients Undergoing Coronary Artery Bypass Surgery

Abstract: Background: Nonpulsatile blood flow plays an important role in the pathogenesis of renal dysfunction in patients with extracorporeal circulation. In our opinion, hypoxic preconditioning (HP) can be used to protect kidneys from postsurgical dysfunction. The aim of this study was to evaluate nephroprotective efficacy of HP in myocardial revascularization with extracorporeal circulation. Methods: The randomized, controlled trial was performed in 63 patients undergoing coronary artery bypass grafting (CABG). Thirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…1 Despite extensive research, therapies for AKI are still lacking in clinical practice. In contrast, preventive strategies using various so-called preconditioning protocols, including caloric restriction (CR) and interventions activating hypoxia signaling (ischemic preconditioning [IP] and hypoxic preconditioning [HP]), [2][3][4] have been found to be extraordinarily effective in animal models. Although it has long been known that CR 5 and activation of hypoxia signaling 6,7 lead to an extension of healthy lifespan, more recent experiments demonstrated that a short-term application of CR or IP/HP induces robust protection of various organs, including heart, 8 kidney, 9,10 brain, and liver.…”
Section: Resultsmentioning
confidence: 99%
“…1 Despite extensive research, therapies for AKI are still lacking in clinical practice. In contrast, preventive strategies using various so-called preconditioning protocols, including caloric restriction (CR) and interventions activating hypoxia signaling (ischemic preconditioning [IP] and hypoxic preconditioning [HP]), [2][3][4] have been found to be extraordinarily effective in animal models. Although it has long been known that CR 5 and activation of hypoxia signaling 6,7 lead to an extension of healthy lifespan, more recent experiments demonstrated that a short-term application of CR or IP/HP induces robust protection of various organs, including heart, 8 kidney, 9,10 brain, and liver.…”
Section: Resultsmentioning
confidence: 99%
“…For example, HPC induced neuroprotection against transient global cerebral ischemia in adult rats [10]. Furthermore, a recent clinical trial found that a 10-min HPC could protect the kidneys from ischemic injury and postsurgical dysfunction in patients undergoing coronary artery bypass surgery [14].…”
Section: Introductionmentioning
confidence: 99%